Review Article: Toward Future Particulate Matter Situations in Thailand from Supporting Policy, Network and Economy. Issue 1 (31st January 2020) - Wongwatcharapaiboon, Jitiporn
In the era of climate uncertainty in 2019, PM2.5 situations in Thailand are considered as big impacts to local livings in terms of health and well-being. This paper aims to investigate policies to decrease PM2.5 levels and to examine reliable networking systems. International and domestic policies are literally found for controlling traffic emission, open burning activities, public health and industrial zoning, when strong satellite networks can be proved by the reliability and accuracy of PM2.5 data collections, sources and chemicals identifications. Turning to financial loss during the PM2.5 situation, cost estimations have been accounted in terms of environmental tax, pollution footprint, health mortality, public air cleaning payment, GDP and uncertainty cost of air pollution. The results related to policy can affect local social interventions, if policies match correctly to suitable techniques in this research series. Also real-time prospective warning of local PM2.5 exceeding is required with accuracy, while all applicable methods are financially comparing in different contexts.